Pediatric Nurses' Experiences of Identifying and Managing Constipation in Hospitalized Children - (:unkn) unknown (My University, 2018)
Pediatric nurses care for hospitalized children with constipation daily. Pediatric nurses’ timely identification and management of constipation in hospitalized patients can be key to preventing long-term problems with chronic constipation and promoting child well-being. The purpose of the study was to investigate the experiences of pediatric nurses regarding their identification and management of constipation in hospitalized children. The Theory of Planned Behavior (TBP) informed this qualitative study. Participants for this phenomenological investigation were 21 pediatric nurses. Nurses provided care in the inpatient setting in a freestanding 292 bed magnet-designated pediatric hospital. In depth interviews were conducted to explore participants’ perspectives of their experiences caring for hospitalized children with constipation. Six themes emerged from the results: 1) Looking for clues of constipation with subthemes of a) typical bowel patterns, b) walking kind of funny, and c) different reasons why they’re constipated; 2) Multiple, multiple interventions with subthemes of a) go and sit on the toilet, b) a wide variety of constipation management, and c) it just took educating; 3) Getting everybody on the same page with subthemes of a) the parents are a huge resource, b) they trust our judgment, and c) just kind of negotiate; 4) Down there with subthemes of a) I would not automatically do a rectal check, b) an infant is totally different from a 5 or 6-year old, c) I just try and build a trustful rapport, d) comfort and privacy, and e) we kind of do a dress rehearsal at the desk; 5) Just a very basic overview of constipation with the subthemes of a) you need time, experience, and certain patient situations and b) the unit I work on; and 6) Experiences whether good or bad with subthemes of a) it’s exhausting, b) people missed it, and c) I know it will help the child. Participants described their ability to recognize constipation in children across all ages. Pediatric nurses were creative in promoting bowel elimination through non-pharmacologic interventions, yet found pharmacologic constipation management challenging. Oral medications were easier for nurses to administer, which can influence the timely resolution of constipation. Participants didn’t like to give enemas or suppositories and were uncertain about performing rectal checks and disimpactions. Pediatric nurses reported that child and parent negotiation was required to influence outcomes in the care of hospitalized children with constipation. Nurses in this study found that years of experience, especially on their work unit, enhanced their knowledge of constipation. According to the participants, constipation identification and management in hospitalized children can be exhausting but rewarding. Nurses needed to negotiate to promote successful outcomes. Implications for nursing practice, education, policy and future research are discussed.
Keywords: Attitudes; Constipation; Hospitalized Children; Intimate Touch; Nursing; Pediatrics